Group Guidance Based on Werewolf Game to Improve Students' Interpersonal Communication Skills - Yasintha Sari Pratiwi; Wahyu Widyatmoko; Ria Safaria Sadif; Eldzaka, Rollanda Gharry (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study was designed to test the extent to which game-based group guidance using Werewolf could enhance the interpersonal communication skills of junior high school students. Employing a one-group pretest-posttest method, seven students were selected through purposive sampling based on low interpersonal communication assessment scores. An interpersonal communication scale with proven validity and reliability was used as the instrument. Data analysis included the Shapiro Wilk normality test, the paired sample t-test for difference testing, and the calculation of Cohen’s d effect size. The research findings revealed an increase in the average interpersonal communication score from 89.57 to 120.57, with a significant difference (p < 0.05) and an effect size value of d = 3.28 (large effect category). This indicates that the Werewolf game played a role in facilitating reciprocal communication, argumentation, empathy, and teamwork. The implication of this research is that role-playing-based Werewolf games can be an effective choice of group guidance media for junior high school students.